The Effect of Thermal Annealing on the Diffusion Profile of Nickel in GaAs Substrates - Aseel A.K. Hadi (Engineering and Technology Journal, 2009)
Diffusion of nickel in GaAs has been studied at 950ºC. The diffusion wasenhanced during limited interval and for different quantities of As. Nickel atomshad diffused in the beginning due to the interstitial movement of atoms but largenumber of nickel atoms occupies substantial locations in p-type GaAs lattice.Measurements performed to the samples have showed good agreement between thenickel atoms concentration and majority charge-carriers in p-type semiconductor(holes). Measurements explained that electrical conductivity of p-type samples wasnot due to system heating but to the diffusion of nickel atoms occupying sites ofgallium atoms.